CELAH KEAMANAN KREDENSIAL WINDOWS PADA GOOGLE CHROME - Sayed Achmady, Maryanti (Jurnal Sains Riset, 2019)
An attack that can leak authentication credentials on a Windows operating system by using the SMB file sharing protocol on a Windows operating system is an ever-present problem. It's been exploited in many ways, but the only solution found is limited to local area networks. Jonathan Brossard and Hormazd Billimoria recently presented one study involving internet attacks at the Black Hat security conference in 2015. However, no SMB-related attacks were published. In this paper, we will explain how an attack can cause Windows credential theft, which may affect the default configuration in Google Chrome browser.Key words— Kredensial Windows, Google Chrome, Vulnerability